Prognostic Factors for Open Globe Injuries and Correlation of Ocular Trauma Score in Tianjin, China - Yu Meng; Hua Yan (Journal of Ophthalmology)
Purpose. To investigate prognostic factors that influence the final visual acuity (VA) and to correlate the ocular trauma score (OTS) with the final VA in open globe injuries. Methods. A retrospective review of 298 patients with open globe injuries admitted to Tianjin Medical University General Hospital was carried out from January 1, 2010, till December 31, 2014. Prognostic factors influencing the final VA in patients with open globe injuries and the correlation between OTS and the final VA were examined. Results. Three hundred and fourteen eyes from 298 patients with open globe injuries were analyzed. Males had a higher rate of open globe injury than females (83.56% versus 16.44%). Mean age was 45.46 ± 17.48 years (5–95 years). In a univariate analysis, prognostic factors influencing the final VA included initial VA, relative afferent papillary defect (RAPD), vitreous hemorrhage, lens injury, endophthalmitis, hyphema, retinal detachment, and the zone of injury. In a multiple logistic regression analysis, initial VA, RAPD, and the zone of injury were considered to be independent risk factors. The OTS correlated with final VA (r=0.988, p=0.000). Conclusion. In our study, the most important prognostic factors influencing the final VA were initial VA, RAPD, and the zone of injury. The OTS was of great importance for patients and ophthalmologists.